AB1322 Treatment response as a predictor for refractory disease and/or transition to rheumatoid arthritis in patients with polymyalgia rheumatica. (12th June 2018) - Hayashi, K.; Ohashi, K.; Watanabe, H.; Sada, K.-E.; Asano, Y.; Hiramatsu, S.; Yamamura, Y.; Miyawaki, Y.; Morishita, M.; Matsumoto, Y.; Kawabata, T.; Wada, J.
Abstract : Background: Polymyalgia rheumatica (PMR) is a common inflammatory rheumatic disease that affects elderly people and predominantly causes shoulder and pelvic girdle pain. PMR is sometimes refractory 1), and some cases are finally diagnosed with rheumatoid arthritis (RA) 2). Predictive factors for clinical course of PMR are not fully elucidated. Objectives: The purpose of this study is to elucidate predictive factors for clinical course of PMR. Methods: Newly diagnosed PMR patients at our hospital from July 2006 to June 2017 were enrolled. All patients fulfilled the EULAR/ ACR 2012 Provisional Classification Criteria for PMR but not the EULAR/ ACR 2010 Classification Criteria for RA. Patients who had GCA, other rheumatic disorders like SLE or were newly diagnosed with cancer within 2 years of dignosis were also excluded. The primary endpoint was the remission by one month after commencement of treatment. Remission was defined as the absence of PMR symptoms and the elevation of erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP). For evaluation of the composite outcome of refractory PMR and final diagnosis of RA, the secondary outcome was defined as requirement of additional treatment and/or relapse during the observation period. Relapse was defined as a flare of PMR symptoms and the elevation of ESR or CRP. Categorical variables with a possible relation to the outcomes such as clinical characteristics, criteria items, articular symptoms and laboratory data were compared by using the nonparametric chi-square test. Results: The mean age of enrolled 61 patients was 70.6 years and 67% were female. 38 (62%) patients failed to achieve remission by one month. The proportion of patients showing elevated ESR (>100 mm/h) at baseline was higher in patients without remission than those with remission (62% vs. 30%, p=0.017) though there were no differences in sex, articular symptoms. Patients without remission also showed a lower reduction rate of CRP after a week (76% vs. 89%, p=0.026) compared to those with remission. Furthermore, 30 (49%) patients required additional treatments and/or had relapses during the observation period. These patients showed higher platelet counts at baseline (42.9±1.9 vs. 36.3±2.0 × 10 4 /mm 3, p=0.023) and lower proportion of achievement of CRP levels less than 1.0 mg/dl after a week (44% vs. 80%, p=0.009). Conclusions: ESR and platelet counts at baseline and early treatment response might be useful for prediction of refractory PMR and/or transition to RA. References: [1] González-Gay MA, Matteson EL, Castañeda S. Polymyalgia rheumatica. Lancet. 2017; 390(10103): 1700–1712. [2] Hutchings, A., Hollywood, J., Lamping, D. et al. Clinical outcomes, quality of life, and diagnostic uncertainty in the first year of polymyalgia rheumatica. Arthritis Rheum2007; 57: 803–809. Disclosure of Interest: None declared